Quadriplegia due to Spinal Subdural Abscess (Journal of Medicine, 2009)
Spinal subdural abscess (SSA) is a very rare cause of quadriplegia. According to the site of involvement, they may present with paraplegia or rarely quadriplegia. The most common site is thoraco-lumber region, but our patient presented with cervical SSA. We should consider it as a medical emergency because early diagnosis and prompt treatment can save the life and prevent residual disability of the patient. Â  doi:10.3329/jom.v10i1.1998 Â  J Medicine 2009; 10: 20-21